Can We Think Computation in Images or Numbers? Critical Remarks on Vilém Flusser's Philosophy of Digital Technologies. - Krtilova, Katerina (Flusser Studies, 2016)
The article discusses the critical view of the philosopher and writer Vilém Flusser's philosophy of digital technologies including Flusser's vision of the universe of computation as similar to the philosopher Friedrich Kittler's view on computer technology and its impact on knowledge and perception.